rDNA Loci Evolution in the Genus Glechoma (Lamiaceae) - Jang, Tae-Soo (PLoS One, 2016)
Glechoma L. (Lamiaceae) is distributed in eastern Asia and Europe. Understanding chromosome evolution in Glechoma has been strongly hampered by its small chromosomes, constant karyotype and polyploidy. Here phylogenetic patterns and chromosomal variation in Glechoma species are considered, using genome sizes, chromosome mapping of 5S and 35S rDNAs by fluorescence in situ hybridisation (FISH), and phylogenetic analyses of internal transcribed spacers (nrITS) of 35S rDNA and 5S rDNA NTS sequences. Species and populations of Glechoma are tetraploid (2n = 36) with base chromosome number of x = 9. Four chromosomes carry pericentric 5S rDNA sites in their short arms in all the species. Two to four of these chromosomes also carry 35S rDNA in subterminal regions of the same arms. Two to four other chromosomes have 35S rDNA sites, all located subterminally within short arms; one individual possessed additional weak pericentric 35S rDNA signals on three other chromosomes. Five types of rDNA locus distribution have been defined on the basis of 35S rDNA variation, but none is species-specific, and most species have more than one type. Glechoma hederacea has four types. Genome size in Glechoma ranges from 0.80 to 0.94 pg (1C), with low levels of intrapopulational variation in all species. Phylogenetic analyses of ITS and NTS sequences distinguish three main clades coinciding with geographical distribution: European (G. hederacea–G. hirsuta), Chinese and Korean (G. longituba), and Japanese (G. grandis). The paper presents the first comparative cytogenetic analyses of Glechoma species including karyotype structure, rDNA location and number, and genome size interpreted in a phylogenetic context. The observed variation suggests that the genus is still in genomic flux. Genome size, but not rDNA loci number and distribution, provides a character for species delimitation which allows better inferences of interspecific relationships to be made, in the absence of well-defined morphological differentiation.